The Impact of Environmental, Social, and Governance Disclosure on Firm Value with Profitability as a Moderating Variable - Tansil, Verica Frangsisca; Tangke, Paulus (AJAR, 2025)
The purpose of this research is to analyze the effect of environmental, social, and governance (ESG) disclosure on firm value. This study also analyzes profitability as a moderator of the influence of environmental, social, and governance (ESG) disclosure on firm value. This research uses stakeholder theory and signaling theory to explain the relationship between the variables. The population used in this research were non-financial companies listed on the Indonesia Stock Exchange during the 2021-2023 period. This study used a purposive sampling method for sample selection. The sample size was 92 companies. The analytical method used in this research was moderated regression analysis, and hypothesis testing was conducted using a partial t-test. The results of this research indicate that environmental, social, and governance (ESG) disclosure have a positive and significant effect on firm value. Profitability strengthens the influence of environmental, social, and governance (ESG) disclosure on firm value by acting as a quasi-moderator.